SELECTED INDONESIAN MICROBES POTENTIALS FOR MEOR - S. Kadarwati; M. Udiharto; Noegroho Hadi Hs; Indria Doria (Testing Center for Oil and Gas LEMIGAS, 2002)
Oil recovery can be increased through the activities of microbes in a process known as Microbial Enhanced Oil Recovery (MEOR). MEOR technology has been implemented in a number of oil producing companies and has proven to have a good prospect, environmentally friendly and low cost. The microbes which proliferate in Indonesian oil fields should be subjected to laboratory identification. Samples of formation water, oil, and soil were taken from various oil fields. These oil fields were selected on account of their reservoir temperatures which promise optimum growth of microbes. In order that MEOR can be applied in these oil fields, the existing microbes in their oil wells were isolated and identified. Based on the results of isolation and identification activities several indigenous bacteria species were obtained from the oil well environment. The potential of each bacteria species for use in MEOR process depends on their ability to live and grow in the reservoir environment as well as the bioproducts produced, such as biosurfactant, bioacid, and biosolvent. The bioproducts produced depend on the inherent capability of the isolate as well as the support of the medium and environmental condition. From the tests of their capability to grow in hydrocarbons, and live in semianaerobic condition, 12 isolates, were selected and some isolates were found to produce such bioproducts. The selected microbes and nutrient have been experimented by using microbial core flooding apparatus. The result has a good prospect for implementation in the oil field.